(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aims to examine the relationship of correlation and impact between strategic foresight as an independent (explanatory) variable and corporate governance as a dependent (responsive) variable, through their respective dimensions. The dimensions of strategic foresight include environmental scanning, strategic choice, and integration capability, while the dimensions of corporate governance comprise the effective governance framework, board of directors’ responsibilities, the role of stakeholders in organizational governance, as well as disclosure and transparency. The study was conducted at the Baghdad Provincial Council. The study population included all departments and committees within the Council. A purposive sample was selected, consisting of administrative leaders, including directors, heads of departments, officials of divisions and units, and heads of permanent committees (such as the Health Committee, Electricity Committee, Services Committee, etc.). The researcher adopted a descriptive-analytical approach. A questionnaire was used as the primary data collection tool, consisting of (42) items distributed across the study variables. The number of valid responses analyzed reached (77) out of (85) distributed questionnaires, in addition to diagnosing the actual situation of the organization under study. The study was guided by the following central question: To what extent does strategic foresight influence the enhancement of corporate governance in the Baghdad Provincial Council? This question served as a starting point for exploring the research problem. Accordingly, the study is considered exploratory in nature, aiming to investigate and understand the relationship between the dimensions of the two variables. A range of statistical methods was employed, including the mean, standard deviation, relative importance, Cronbach’s alpha, McDonald’s omega, coefficient of determination, Spearman’s rank correlation coefficient, Z-test for the significance of the correlation coefficient, T-test, and F-test. The analysis was conducted using statistical software such as SPSS (V28), Smart PLS (V4), and Microsoft Excel (2010). The most prominent finding of the study indicates that the integrative results reveal a significant relationship between the weakness of the leadership dimension in corporate governance and the level of maturity of strategic foresight. The absence of effective strategic leadership limits the transformation of foresight practices into well-established institutional policies.